Effective healthcare and the challenges of resource-poor societies - Borodo, M. M. (Nigerian Journal of Basic and Clinical Sciences, 2026)
Determinants of efficient healthcare include appropriateness of care to the setting, a well-informed and adequately sensitized healthcare products consumer population, an enabling environment to deliver the care, and finally an adequately trained and well-motivated healthcare delivery team – all of these in an appropriate mix to produce the desired satisfactory results. In the context of the developing world, satisfactory healthcare for the populace has remained challenging and illusionary because of varying shortcomings of the above-mentioned factors as reflected in the current level of care in the region, as is well captured in the articles reported in the current edition of the journal.